2018
DOI: 10.17576/3l-2018-2401-07
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Oral Communication Strategies Used by a Group of Nepalese Adult Learners in an ESL Context

Abstract: This paper sought to examine the oral communication strategies (CSs) used by a group of Nepalese adult learners in an oral task in an ESL context. There has been a long history of CS studies in L2 acquisition research; however, there are no studies yet reporting the CSs employed by Nepalese learners in an ESL context. Hence, six Nepalese learners with intermediate language proficiency were engaged in a picture storytelling task. Their narrations were recorded and transcribed, and their responses during the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 20 publications
(39 reference statements)
0
13
0
6
Order By: Relevance
“…The findings showed that the storytelling task-based teaching method was found useful for the development of adult learners' oral communication skills in the Nepalese context. (Manzano, 2018).…”
Section: Figure 5 Hierarchy Chart Of Teaching Methodsmentioning
confidence: 99%
“…The findings showed that the storytelling task-based teaching method was found useful for the development of adult learners' oral communication skills in the Nepalese context. (Manzano, 2018).…”
Section: Figure 5 Hierarchy Chart Of Teaching Methodsmentioning
confidence: 99%
“…Additionally, Zhang (2012) conducted a study about the effectiveness of strategy-based instruction towards listening comprehension including many of Oxford's strategies like the cognitive, metacognitive, and social strategies. Results showed that employing these strategies by EFL teachers increased positively the listening comprehension of students, and leverage the communication skills of EFL learners because EFL learners acquire more knowledge of the language while practicing listening comprehension, so their speaking competence will be better (Manzano, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, a study of procedural deviation in aviation discourse with the aim of coming up with a typology of deviations in aviation English could be useful for local trainers and material developers. Researchers could investigate the communication strategies (see methodology used by Manzano, 2018), and attitudes and motivation to study aviation English of controllers who regress into plain English (see Quinto (2015)'s study on attitude and motivation to study a working language).…”
Section: Further Researchmentioning
confidence: 99%